Primary bone solitary B-cell lymphoblastic lymphoma aberrant expression Fli-1 and ERG: A case report - Huan Chen; JiaSi Li; Yong Huang (Indian Journal of Pathology and Microbiology)
Primary non-Hodgkin bone lymphoma is a rare disease, and within this category, B-cell lymphoblastic lymphoma (B-LBL) is an even rare clinical entity that has only been reported in small case series or individual case reports. B-LBL can mimic Ewing’s sarcoma both clinically and histologically, leading to misdiagnosis. We present a case of primary B-LBL of the bone in a 7-year-old girl. The tumor cells are uniform and small with a diffuse and infiltrative growth pattern similar to EWS. Immunohistochemical results are positive for CD99, Fli-1, ERG, TDT, PAX5, and CD79α, but negative for leukocyte common antigen, CD3, CD20, and NKX2.2. No other lesions are found on positron emission tomography/computed tomography imaging. Finally, primary solitary bone B-LBL of the right tibia was diagnosed.